Os territórios sonoros da paulicéia e a influência da cultura Sound System - Freitas, Guilherme Vieira de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The sound system culture arose in the 1960s in Jamaica, having as its main objective to take music to the streets. For a very long period of time, sound system culture reproduced in the Caribbean island, when in the end of the 1970s the rhythm reached out to the youth that lived through the spirit of May 1968 and seeked for new ways to act politically and new lifestyles. The movement reached the city of Sao Paulo in the early 2000s with Dubversão Sound System. Despite the city owning, nowadays, over ten sound systems spread across town, there are still no studies regarding this front that has been adding more and more young people from other urban tribes such as hip-hop and punk, and bringing leisure and culture to both downtown and the outskirts of town. In that manner, this research aims into analyzing the historical formation of reggae and its influences in the city of Sao Paulo's youth movements, using Sound System as a form of spatiality in the territory

A Cultura Sound System surgiu na década de 1960 na Jamaica, e tinha como principal funçãolevar música para o povo na rua. Durante muito tempo essa cultura se reproduziu na ilhacaribenha, até que no final da década de 1970 esse ritmo acabou ganhando o gosto de muitosjovens que viviam o espírito de maio de 1968, buscando novas formas de atuar e novos estilosde vida. Esse movimento chegaapenas na primeira década de 2000 na cidade de São Paulocom o Dubversão Sistema de Som. Mesmo a cidade possuindo hoje em dia mais de umadezena de Sistemas de Som espalhados, ainda não há estudos sobre movimento que vemagregando cada vez mais jovens vindos de outros movimentos como o hip-hop e o punk, elevando lazer e cultura tanto para o centro quanto para a periferia da cidade. Assim, essetrabalho visa analisar a formação história do reggae e suas influencias nos movimentos juvenis da cidade de São Paulo, usando assim o Sound System como sua forma de espacialidade no território
Keywords: Adolescência - Aspectos sociológicos; Música popular - Jamaica; Reggae (Música); Música - História